EVALUASI ESTETIKA AIR PANCURAN PADA TAMAN SUROPATI; SEMANTIC DIFFERENTIAL DAN SCENIC BEAUTY ESTIMATION - NURJANNAH HAMDANI (LPPM, 2017)
Garden andfountain elementhave important roleto be one of the landscape aestetic determinat. Fountain element gives aestetic value, improves the quality, andenhance the garden character. The shape of fountainalso influence the aestetic of garden and gives higher value to visual aestetic. To rate the aestetic beauty, this research method used Scenic Beauty Estimation (SBE ) andSemantic Differential (SD) analysis. The aims of the researchare : 1) to observe and 2) to evaluate the visual aestetic quality from different viewpoint of fountain in a garden. The result showed different viewpoint that influence the aestetic assessment of an object. From the eight (8) different viewpoints give different impression and also different aestetic score. Three (3) category are obtained SBE assessment are : 1) the highest score from photo 6 (score 70.657), 2)The medium score from photo 2 (score 42.328), and 3) the lowest score from photo 5 ( score 43.819). From Semantic Differential, the lowest aestetic score also showed from photo 5 viewpoint.It showed the narrow, dark, disorientation, closed, vague, invisible, and random impression. It is matching with our expectation because the lowest SBE score also from landscape viewpoint of photo 5.